Implementation of Freundlich Equation Absorption of Calcium and Magnesium Ions on Saturated Salt Solution - C. Pujiastuti; K. Sumada; Y. Ngatilah; D. I. Putri; N. N. W. Triana (Nusantara Science and Technology Proceedings)
Traditional salt contains NaCl between 80-92% and the other is impurity such as magnesium (Mg), calcium (Ca), potassium (K) and sulfate (SO4) ions., The NaCl content of salt is under government regulations, namely NaCl 94.7% for consumption salt and NaCl above 98% for industrial salt. Improved salt quality is done through increasing NaCl concentration or decreasing concentration of impurities. In this research, salt quality improvement was carried out by reducing the concentration of impurities through ion exchange methods. The ion exchange method is carried out by using 2 (two) types of resin namely cationic resin and anion. Cationic resin serves to exchange positively charged ions such as Mg2+, Ca2+ and K+ ion and anionic resin for negatively charged ions such as SO42-. The purpose of this study is to obtain Freundlich mathematical equations which can be used to calculate resin requirements. The study was conducted using a stirred tank with a variable amount of cationic resin from 25-150 grams per 1 liter of saturated salt solution and stirring time of 5 - 30 minutes. The saturated salt solution used contains 28.4% NaCl, 0.4% calcium and 0.09% magnesium. The results obtained were 36.99% NaCl, 0.025% Calcium and 0.044% Magnesium, 25 minutes contact time, 100 grams cation resin Freundlich equation obtained Calcium ion: ln (x / m) = 1.087 ln C - 4.2282, R2 = 0. 9544, Magnesium Ion: ln (x / m) = 5.6278